2019
DOI: 10.1002/lary.28298
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Epithelial Adenomatoid Hamartoma is Frequent in Olfactory Cleft After Nasalization

Abstract: ObjectivesTo assess the site and histopathology of polyps at the first revision surgery for recurrent nasal polyposis (NP) after radical ethmoidectomy (nasalization).Study DesignRetrospective study.MethodsBetween January 2008 and December 2015, a total of 62 patients having undergone revision surgery for recurrent NP after nasalization were included. The site and histology of the recurrence of polyps were analyzed according to operative and pathological reports.ResultsHistology showed classical inflammatory na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…As for recurrence of REAH, it was reported that 15 of 363 (4%) patients had recurrence of REAH, and all of them required reoperation 6 . Another study demonstrated REAH in 8.9% of nasal cavities at primary surgery versus REAH in 54.8% at revision surgery, meaning that REAH is found more frequently at revision surgery 30 . In our study, postoperative mucosal thickening and polyp recurrence were more likely to occur in the REAH group.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…As for recurrence of REAH, it was reported that 15 of 363 (4%) patients had recurrence of REAH, and all of them required reoperation 6 . Another study demonstrated REAH in 8.9% of nasal cavities at primary surgery versus REAH in 54.8% at revision surgery, meaning that REAH is found more frequently at revision surgery 30 . In our study, postoperative mucosal thickening and polyp recurrence were more likely to occur in the REAH group.…”
Section: Discussionsupporting
confidence: 45%
“… 6 Another study demonstrated REAH in 8.9% of nasal cavities at primary surgery versus REAH in 54.8% at revision surgery, meaning that REAH is found more frequently at revision surgery. 30 In our study, postoperative mucosal thickening and polyp recurrence were more likely to occur in the REAH group. However, no reoperation cases have been diagnosed with REAH, and no REAH cases have yet required reoperation.…”
Section: Discussionsupporting
confidence: 45%
“…Patients with isolated- and associated-REAH also differed in the rate of prior ESS, a factor that has been linked with OC opacification and REAH development. 2325 Overall, 53.8% of patients in this study underwent ESS prior to identification of REAH. Patients with isolated-REAH had lower rates of prior ESS (25%) compared to those with associated-REAH (66.7%).…”
Section: Discussionmentioning
confidence: 97%
“…REAH can exist in isolation or association with other inflammatory processes, with nasal polyps (NP) being the most frequent 5,7 . In previous reports, REAH is found in about 30% to 55% of patients who undergo primary or revision surgery for NP 3,8–10 . In addition, REAH and CRSwNP are easily confused in terms of symptoms.…”
Section: Discussionmentioning
confidence: 99%